The image of Latin America as perceived by Southern Cone diplomats - Otero, Delia del Pilar (Centro de Investigaciones de la Facultad de Filosofía y Humanidades, 2006)
During the second half of 19th century and the beggining of the 20th century a set of ideas which would reach unpredictable repercussions started to acquire importance in Latin America. We refer to nationalisms. They spread over Latin American countries in relation with different variables such as political and social changes or international situation, which gave many opportunities to express hostility against the foreign or different. The mentors of nationalisms were engaged in the construction of a nation. For that purpose it was necessary, among other things, to make clear that even if they all were Latin Americans they didn’t share the same characteristics. With regard to that issue, this article proposes to analyze a representative sample of diplomatic writings which were produced in the Southern Cone. We consider them as a modality of political discourse as well as an efficient instrument of the construction of a particular image of the other. Although these writings constituted the expression of a group of public officials who addressed their message to a limited addressee, such as the chancelleries of their countries, who enunciated these discourses were also journalists, men of letters or intellectuals who spread their ideas to wider social sectors. In that way, they facilitated the appropriation and permanence of these discourses in other social sectors of national societies.